2019
DOI: 10.1186/s12891-019-2397-3
|View full text |Cite
|
Sign up to set email alerts
|

Burden of shoulder and/neck pain among school teachers in Ethiopia

Abstract: BackgroundShoulder and neck pain are reported as the most common occupational-related health problem and cause of morbidity, absenteeism from work among school teachers worldwide. School teachers represent an occupational group, who are exposed and appears to have prevalent shoulder and/or neck pain due to their daily work tasks and the nature of work. There is a scant epidemiological study regarding shoulder and neck pain among school teachers in Ethiopia. Therefore, this study was set out to assess the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
1
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 25 publications
2
46
1
19
Order By: Relevance
“…Further, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled towards the life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Further, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled towards the life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Further, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled towards the life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%